A study of the labour market of renewable sources of energy in Poland - Graczyk, Alicja Małgorzata (Economics of the 21st Century, 2014)
The main purpose of the article is to analyse the renewable energy sources labour market in the country based on the example of survey studies conducted in Lower Silesia in 2010 commissioned by the Marshal’s Office. The author took part in the discussed project as a member of the research team and is the co-author of the final publication. The study was conducted as part of a project by the Department of Economic Development of the Marshal’s Office of the Lower Silesian Voivodeship in 2010 entitled “Prognoses and analyses of the potential of the Lower Silesia to use renewable energy sources”. The article has analysed the following: employment in the RES sector, revenues and savings due to RES, and human resources. The author has also identified the pro-employment effects in the RES sector on the domestic and EU markets; she has also made prognoses for the demand for work in the RES sector. Study results show that the increase of employment in the sector resulting from the increase in production and installed power shall be related to biomass, solar power, and wind power technologies. From the data pertaining to employment in Lower Silesia one may conclude that the RES sector employs mostly specialists, managers, and physical labourers. Unmet demand for physical workers in the forestry and agricultural sectors is visible
Ekonomia XXI Wieku = Economics of the 21st Century, 2014, Nr 4 (4), s. 116-125
Keywords: renewable energy sources; labour market; investigations; odnawialne źródła energii; rynek pracy; badania